Lymphomatoid papulosis: an update and review. (14th October 2019) - Martinez‐Cabriales, S.A.; Walsh, S.; Sade, S.; Shear, N.H.
Abstract: Lymphomatoid papulosis (LyP) is a benign chronic often relapsing skin condition that belongs to the CD30‐positive cutaneous lymphoproliferative disorders. LyP typically presents as crops of lesions with a tendency to self‐resolve, and morphology can range from solitary to agminated or diffuse papules and plaques to nodules or tumours. The clinical–histological spectrum can range from borderline cases to overlap with primary cutaneous anaplastic cell lymphoma (pcALCL). Histology and immunophenotype commonly show overlap with other CD30‐positive disorders and sometimes may be identical to pcALCL, making its diagnosis more difficult. Patients with LyP have an increased risk of developing a second neoplasm such as mycosis fungoides, pcALCL and/or Hodgkin lymphoma. Clinical correlation allows its proper classification and diagnosis, which is fundamental for treatment and prognosis. This review focuses on the clinical appearance, histopathological features, diagnosis, differential diagnosis and management of LyP.